2014
DOI: 10.1002/j.1556-6978.2014.00052.x
|View full text |Cite
|
Sign up to set email alerts
|

A Grounded Theory of Counseling Students Who Report Problematic Peers

Abstract: All counselors, including students, are responsible for intervening when a colleague shows signs of impairment. This grounded theory study investigated experiences of 12 counseling students who reported problematic peers. An emergent theory of the peer reporting process is presented, along with implications for counselor educators and suggestions for future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…To protect the anonymity of respondents in an online study focused on graduate students in a single state, “the researchers did not collect information regarding two other important facets of the participants—characteristics of the institutions they attended and their general geographic location” (Byrne & Shufelt, 2014, p. 186). Although this article and Parker et al (2014) both noted anonymity as an issue, its effect was quite different in each study and necessitated using this code in both themes.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…To protect the anonymity of respondents in an online study focused on graduate students in a single state, “the researchers did not collect information regarding two other important facets of the participants—characteristics of the institutions they attended and their general geographic location” (Byrne & Shufelt, 2014, p. 186). Although this article and Parker et al (2014) both noted anonymity as an issue, its effect was quite different in each study and necessitated using this code in both themes.…”
Section: Resultsmentioning
confidence: 81%
“…This limitation was mentioned in only two of the articles we reviewed, and the way in which it was limiting in the study was different in each case. The study included here as a code within the recruitment theme noted that lack of anonymity influenced self‐selection and participation in the study: “more than one participant responded to our study from an anonymous e‐mail account that was created expressly to provide anonymity to study participants” (Parker et al, 2014, p. 123).…”
Section: Resultsmentioning
confidence: 99%
“…In a review of the literature, only seven published studies considered students perspectives, with two in counselor education (Gaubatz & Vera, ; Parker et al, ) and five in psychology (Mearns & Allen, ; Oliver, Bernstein, Anderson, Blashfield, & Roberts, ; Rosenberg, Getzelman, Arcinue, & Oren, ; Shen‐Miller et al, ; Veilleux, January, VanderVeen, Reddy, & Klonoff, ). Mearns and Allen () noted from survey data that 95% of students ( N = 73) acknowledged knowing a student with professional deficits, and 42% indicated that they had confronted the student of concern.…”
Section: Research Investigating Students' Perspectivesmentioning
confidence: 99%
“…Approximately two thirds of the sample stated that they were unsure if their program had a policy in place to address students of concern. Parker et al () interviewed current and former counselor education students ( N = 12) to develop a theory of peer reporting of gatekeeping concerns. Students in the study expressed a need for clear protocols for reporting peers and believed that programs can reduce the number of gatekeeping issues by improving the admissions process.…”
Section: Research Investigating Students' Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation